Managing Corporate Brands A new approach to corporate communication - Marcos OrmeÃ±o (Deutscher UniversitÃ¤ts-Verlag, 2007)
Much attention has been devoted recently to corporate brands and corporate reputations. Companies go to great lengths to enhance their image in the minds of consumers, investors, employees, community members and other constituencies. These constituencies, previously informed about the company almost exclusively by the press and other third parties (e.g. ï¬nancial analysts and governmental ofï¬cials) are increasingly being targeted by corporate advertising and a whole array of ad-like communication activities. Because these â€˜controlled mediaâ€™ are ï¬‚exible and easy to manage, they are essential to the corporate brand-building effort. Despite the important role of corporate advertising and ad-like communication activities in building a corporate brand, current research fails to explain how brand-building corporate communication programmes should be designed. Managers need a more thorough understanding of how to select among the various means of enhancing the image of a company and increasing its awareness. These means of brand communication extend beyond conventional advertising media and include ad-like means such as events, trade shows, and sponsorship. Deciding which corporate communication tools to use is a challenging task because of the large number of alternatives available, the complexity of the communication phenomena and the economic importance of such a decision to a ï¬rm. Current approaches to tool selection mainly lack formalisation or fail to consider how corporate communication works, or both. As a result, managers have to rely on simple rules of thumb for decision-making (e.g. print is the right medium for corporate adverts) and on ï¬‚awed notions of the nature of the communication process (e.g. corporate design increases awareness but does not enhance a companyâ€™s image). The purpose of this research is to provide guidance for using corporate communication in corporate brand management through the development of a decisionmaking model to assist managers in their selection of the appropriate corporate communication tools. This research is structured as follows: after deï¬ning corporate brands and corporate communication, it presents a behavioural stimulusorganism-response framework to explain how corporate communication works. Corporate communication stimuli (e.g. a corporate advert) affect brandknowledge structures in constituenciesâ€™ minds, which in turn may positively affect constituenciesâ€™ responses to the marketing of a corporate brand. Resulting corporate brand knowledge is moderated both by constituency-related factors, x Abstract namely prior knowledge and processing goals, as well as stimulus-related factors, namely modality, message, execution, time and place. This research then develops a managerial decision-making model for selecting the best corporate communication tools available. This model builds on the proposed behavioural framework: brand-knowledge structures serve to specify a modelâ€™s objectives and stimulus-related moderators serve to identify a modelâ€™s multiple attributes upon which alternatives are measured. The proposed decision-making model is then applied to an illustrative problem, which involves selecting from among major corporate communication tools: mass media advertising, corporate design, events, exhibitions, sponsorships and websites. The proposed model seems to be superior to previous approaches for selecting qualitatively different communication tools because it follows a proven method, rests on a strong behavioural basis, allows for more transparent decision-making, structures the selection decision better, reï¬‚ects a managerâ€™s preferences more accurately and can be easily adapted and extended. Finally, this research discusses its contributions to theory and makes suggestions for using corporate communication in corporate brand management.